The usage of E-Wallet among hotels in Malaysia / Aisyah Samian - Samian, Aisyah (2020)
This undergraduate project research is purposely for identifying the factors that affecting the customer’s choice toward E-Wallet in Malaysia. The sample use for this research is the usage of e-wallet among hotels in Malaysia. There are three (3) factors identified to be the independent variable which are the E-Wallet application quality, ease of use E-Wallet application and privacy and security of E-Wallet. The dependent variable will be the customer choices which will be the main objective of this thesis. This research is based on few problems facing by hospitality industry in Malaysia such as the hotel guests not ready to utilize the usage of to rapid growth of E-Wallet in Malaysia is one of the main issues. In this research, we going to identify factors that affects the customer choices towards use E-Wallet in Malaysia among the selected independent variable. This research is going to help the Hotel Industry improvise on services when knowing all the reasons why people choose E-Wallet rather than traditional method. It also positively increases the healthy competitions among all related hospitality industries such as Hotel, Resort, Motel and others potential sector. All the data are collected from previous research by previous researchers.